Design de superfície têxtil a partir do dendê - Portela, Pablo Luís dos Santos (2015)
The purpose of this study is to introduce the palm, Bahia cultural symbolic element, in a different context from the culinary, and bring it to the area of the textile surface design, by authorial creation of standards in a contemporary language. To this end, it sought theoretical and conceptual support in authors who discuss surface design, textile design, printing, fashion, Bahian culture. He tried to understand the involvement of the pattern into two categories of analysis, which were: language and differentiation; cultural and symbolic device. The character of this research highlighted by the interdisciplinary approach, experimental and qualitative, which provided support throughout the trodden path. The study, to build the methodology of deconstruction and reinterpretation, was to follow, explore, play, interpret the palm from the decomposition of its morphological structure for seven months. This procedure was based on the method of decontextualization and recontextualization of contemporary surface design. To place the palm with the culture, fashion and Bahian art, selected authors and by conducting interviews with artists and designers Bahia. Research has developed a long creative process from the palm that has gone through different stages, experiments and records, such as intervention with the collective participation of students enrolled of discipline Artistic Design of UEFS; palm fixation test on paper and fabric; palm dyeing fabric; construction cloths; detailing the period of decomposition of the formal structure of the palm; creation of manuals oil palm observation drawings. Then came the composition of the standards that resulted in the series of prints named "The palm vein", with their respective analyzes of the printed fabrics and discussions of the results.